THE EFFECTIVENESS OF USING GOOGLE CLASSROOM AS A LEARNING MEDIA FOR CLASS V AND VI STUDENTS AT THE MADRASAH IBTIDAIYAH STATE 1 OF BANGGAI - Siti Maulid Datun; Ismawati Doembana (European Journal of Humanities and Educational Advancements, 2022)
The purpose of this study was to determine the effectiveness of the use of Google Classroom as a Learning Media for Class V and VI students at Madrasah Ibtidaiyah Negeri 1 Banggai. The population in this study was the number of students in grades V and VI at Madrasah Ibtidaiyah Negeri 1 Banggai. The sample in this study were 41 respondents who are also the total population of the number of students in grades V and VI taken using the census formula. The data collection methods include primary secondary data. Primary data obtained directly in this study through observation, interviews, questionnaires/questionnaires. While secondary data obtained through books or documentation related to this research. The analytical method used is qualitative data method. The results of this study indicate that the use of Google Classroom as a learning medium is very effective with a percentage of 80% which can be seen in the recapitulation table of respondents’ responses.